IMPLEMENTASI PELAYANAN PERPANJANGAN SURAT TANDA NOMOR KENDARAAN BERMOTOR DI SAMSAT SAMARINDA KOTA - Doddy Triantoro; Aji Ratna Kusuma; Djumadi . (Jurnal Administrative Reform, 2017)
The aim of this study is to analyze the implementation of extension services of motor vehicle registration certificate in SAMSAT Samarinda. The research is using qualitative data analysis tehnique. The result shows that the extension of the service certificate of motor vehicle number based on the Indonesian National Police Regulation No. 05/2012, but practically it did not run well. Due to 7 (seven) parameter, only three items that can be pursued especially in a mechanism of service, accountability and hospitality of police personnel in service. The causes of less service in Samsat Samarinda are limited allocation of operational budgets to support the services, lack of availability of operational support that meets the qualifications required, both in quantity and quality, and availability of police personel with technology skill.